(untitled) (Palíndromo, 2020)
The purpose of this article is to analyze the ornamental power of letters outside their textual environment: when they are depicted in paintings. Having as object of study works by Grão Vasco, it analyzes how a specific type of letters, the initials, adorn the books and those who carry them, being part of the appropriately honorable scenario for such characters.